Factors Affecting Retirement Planning Ability - Fida Muthia; Reza Ghasarma; Sri Andaiyani (Faculty of Economics, Universitas Sriwijaya, 2021)
This study tries to prove whether there is an influence between the level of financial literacy, gender and age of a person on his ability to do retirement planning. This study uses a survey method by distributing questionnaires online. The sample of this research is workers who have not retired or workers who are still working even though they have retired. The sampling technique was purposive sampling with judgment, where the criteria used were workers with an age range of 23-65 years. Data analysis used in this study is ordinal regression. The results of this study found that gender and age had an influence on the ability to plan for retirement, but the level of financial literacy was not found to have an influence on the ability to do retirement planning.